Capital Shift to ASEAN 2025: Maslahah and Mudharat of Capital Markets from an Islamic Economic Perspective - Huda, Miftakul; Wahyudi, Amin (Jurnal Iqtisaduna, 2025)
This study aims to analyze the implications of the 2025 capital shift to ASEAN from the perspective of Islamic economics, particularly in assessing the balance between maslahah and mudharat in capital market activities. The research employs a qualitative approach using secondary data from capital market reports, international publications, and relevant Sharia regulations. The findings reveal that capital inflows positively contribute to maslahah through enhanced real productivity, inclusive financing, and increased sukuk issuance. However, the results also indicate potential mudharat in the form of market uncertainty, speculative tendencies, and systemic volatility risks. These findings underscore the importance of a Sharia-based policy framework to sustain long-term stability in the ASEAN capital market.